Participation and the Dynamics of Power: Neighborhood Meetings in the Somerville Site Plan Approval Process - Gain, Fiona (Tufts University Tisch Library, 2025)
Thesis (M.A.)--Tufts University, 2025.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisor: Christine Cousineau.; Committee: Laurie Goldman.; Keywords: Urban planning, Land use planning, and Public policy